Operating System Concepts / International Student Version - Gagne Greg; Galvin B. Peter; Silberschatz Abraham (Wiley, 2014)
This book provides a solid theoretical foundation for understanding operating systems. Overview, Introduction, Process Management, Multiheaded Programming, Synchronization, Deadlocks, Memory Management, Memory-Management Strategies, Virtual-Memory Management, Storage Management, File System, I/O Systems, Protection and Security, System Protection, System Security, Case Studies, The Linux System, Windows 7, Influential Operating Systems, Appendices.